(untitled) (Gumilyov Journal of Pedagogy, 2025)
This article examines the model of the organization of socio-pedagogical prevention of mental terrorism among students. The relevance of the study is due to the increased risk of extremism and mental terrorism against young people, which leads to serious social consequences. The concept of mental terrorism has been explained on the basis of scientific works considered in the context of higher education. The analysis of the works of domestic and foreign scientists who studied the problems of mental terrorism among young people is carried out, the individual views of the authors are substantiated. The basic principles and approaches to the prevention of mental terrorism in higher education institutions are analyzed, effective forms and methods of working with students are considered. Materials and methods were used, including scientific publications, analysis of normative acts. The laws of the Republic of Kazakhstan concerning mental terrorism are considered. The main aspects of the threat of mental terrorism were grouped, and a model for organizing socio-pedagogical prevention among students was developed. The model, which includes motivational-value, conceptual, content-technological, evaluative-measuring blocks, is focused on the result of the formation of the personality of a student who is psychologically stable, fully informed about mental terrorism, active in social initiatives, has high academic knowledge, is not subject to extremist thoughts and radical ideas.